Flexible and Affordable Foreign Language Learning Environment based on Web 2.0 Technologies - Guetl, Christian; Chang, Vanessa; Edwards, A.; Boruta, S. (Kassel University Press GmbH, 2013)
Web technologies and educational platforms have greatly evolved over the past decade. One of the most significant factors contributing to education on the Internet has been the development of Web 2.0 technologies. These technologies, socially interactive in nature, have much to contribute to the area of Computer Assisted Language Leaning. Unfortunately, Web 2.0 technologies for the most part have been used in an ad hoc manner, permitting language learners acquire knowledge through interaction, but not through a more structured manner as these technologies were not developed to help lean languages as such. The goal of our work is to research and develop an environment, which employs Web 2.0 technology plus online language learning tools to provide a more integrated language learning environment. This paper will explore the technologies and provide information about how tools can be better integrated to provide a more productive working environment for language learners. A first working proof of concept based on our approach introduced is promising supporting modern language requirements and first findings and space for improvements are discussed.